Avaliação dos modelos numéricos para a simulação da secagem de concretos refratários - Moreira, Murilo Henrique (Universidade Federal de São Carlos, 2021)
The drying of hydraulic bonded monolithic refractories is the slowest stage of their application process. Problems related to the control of such a procedure result in cracks, spalling and even, in extreme cases, explosions of the entire lining, and consequently of the industrial equipment. In order to reduce the downtime required during the first heat-up step, an optimization of the drying process is necessary. As the risks involved are considerable, the industry adopts overconservative practices, usually guided by semi-empirical knowledge. In this context, the present work aimed to review the literature, identify the main numerical models, compare them and select the most suitable for this application. This systemic evaluation took place both analytically and by simulating the results for each model comparing them with actual practical experiments. Given the high number of works found during the literature review process, a bibliometric study of this field of knowledge was also proposed. The set of information collected and analyzed indicated that the most common application of such models is for the simulation of Portland cement structures under fire. As a direct consequence, interaction with such researchers is highly recommended. It was also realized that these models could be categorized as those with practical appeal and those with detailed representation of the multiple physical processes that occur in such scenarios, with the main distinguishable difference between such classes being their complexity. Finally, the single-phase model represented the best compatibility with the technological applications and thus its numerical convergence was studied and the sensitivity of the main input parameters was determined. Based on that, the development of a single-phase mesoscale mixed element model was proposed and validated with experimental results, which shows features not yet found in the literature.
Development of numerical models for the simulation of the drying of refractory castables
Keywords: Refratários; Método dos elementos finitos; Secagem; Concreto; Monolíticos; Refractories; Finite element method; Drying; Concrete; Monolithics; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS